Membanding Teori Transformasi Generatif dan Systemic Functional Grammar; Telaah Kritis-Dialogis Antar Madzab Linguistik - Mohammad Andi Hakim (Indonesian Journal of Arabic Studies, 2019)
This paper describes the great tradition of thought that influence the development of linguistic discourse. Between the two of linguistic madzab described in this article is the theory of generative transformation fronted by Noam Chomsky and systemic functional grammar theory initiated by MAK Halliday tradition of thought. The study, conducted a literature study, by using qualitative descriptive study. The data in this paper is a literacy data set obtained from books, articles and journals, as a secondary source to obtain an adequate explanation of the study. This study aims to find a dialogical relationship between the two great streams of linguistics, which although mutual criticism